Development of Systemic Lupus Erythematosus After Infectious Mononucleosis in a 64-Year-Old Woman - Shifang Wang MD; Shiyu Wang MD; Shaleindra Singh MD (SAGE Publishing, 2020)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by heterogeneous symptoms that can manifest in any organ, and often presents at a young age. Infectious mononucleosis (IM) is the acute clinical manifestation of Epstein-Barr virus (EBV). It is characterized by low-grade fever, malaise, lymphadenopathy, splenomegaly, and occasionally symmetrical arthralgias. It has been proposed that EBV is a trigger for new-onset SLE, and patients with autoimmune disorders such as SLE are more likely to have recurrent IM infections. The patient, a 64-year old Caucasian female who's only past medical history was hypertension, developed several months-long period of vague symptoms, including fatigue, malaise, nausea, and nonbilious vomiting with oral intake. She presented with symmetrical polyarthritis involving the hands and elbows, with no history of arthritis before this episode. At the 5-month follow-up, she presented with worsening arthritis bilaterally in her elbows and in her right knee. For several decades, there has been a theoretical association between EBV and SLE, with EBV thought to be one of the many possible triggers for development of SLE. Based on the disease course, we theorize that the patient's IM and EBV infection led to development of SLE. A small fraction of SLE cases have been reported in literature to be associated with EBV. This case adds to that literature with EBV triggering development of SLE in a seemingly previously asymptomatic patient.